Identification of EPHB4 as a potential causal gene and therapeutic target for endometriosis using Mendelian randomization - Shaohua Ling; Delong Xie; Lifang Huang; Siqi Huang; Chun Tian; Liying Huang; Rong Chen; Li Qin; Xiao Qin (Hereditas)
Abstract Objectives Endometriosis is a common condition among women, characterized by chronic pain and infertility, presenting significant challenges for clinicians. This study aims to identify potential druggable targets to offer new therapeutic approaches. Method We utilized the summary-data-based Mendelian randomization (SMR) method to investigate the causal relationships between druggable genes that encode plasma proteins and endometriosis. The data sources included the deCODE database, the UKB-PPP, and the FinnGen database. Colocalization analysis was used to identify whether candidate genes and the disease share a common causal genetic variant. Finally, we measured the protein abundance and relative mRNA expression levels of targeted druggable genes in the plasma and peripheral blood mononuclear cells (PBMCs) of endometriosis patients using ELISA and RT-qPCR. Results By integrating the results of SMR and colocalization analyses, we found that EPHB4 is strongly associated with the risk of endometriosis, with higher levels of EPHB4 correlating with an increased risk of the condition (PFDR < 0.05, PPH4 = 0.99). RSPO3 is moderately associated, with higher levels of RSPO3 correlating with an increased risk of endometriosis (PFDR < 0.001, PPH4 = 0.78). CD109, SAA1, SAA2, FSHB, and SEZ6L2 are weakly associated with endometriosis, with higher levels of FSHB and SEZ6L2 correlating with an increased risk of endometriosis, and higher levels of CD109, SAA1, and SAA2 correlating with a decreased risk of endometriosis (PFDR < 0.05, PPH4 < 0.6). ELISA and RT-qPCR analyses showed that the EPHB4 protein abundance in plasma and mRNA expression levels in PBMCs were significantly higher in the endometriosis group compared to the control group (P-value < 0.05). Conclusions We found that the druggable genes EPHB4, CD109, SAA1, SAA2, FSHB, and SEZ6L2 may be associated with the pathogenesis of endometriosis and are potential therapeutic targets for drug treatment. However, this preliminary study is limited by sample size and population diversity, requiring further validation to confirm the reliability of these findings.